Empowering The Community Through a Herbal Medicine-Based Movement in Pengotan Village, Bali - Winingsih, Gusti Ayu Martha; Batiari, Ni Made Padma; Febriyanti, Ni Made Ari; Noviani, Ni Wayan (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aimed to increase public awareness, knowledge, and skills in utilizing herbal medicinal plants as an alternative for family health maintenance and as a potential source of local economic development. The program was carried out in collaboration with Pengotan Village, Bangli Regency, Bali, involving 50 PKK mothers as participants. It was implemented by a team of lecturers from Kartini Bali Health Polytechnic, who also served as facilitators and resource persons. The activity consisted of six stages: initial observation, provision of tools and materials, pretest, counseling sessions on herbal medicinal plants, posttest, and an evaluation and follow-up stage to assess improvements in participants’ knowledge. Descriptive analysis was used to examine increases in knowledge, planting and processing skills, and understanding of product marketing. The results showed an increase in participants’ knowledge of herbal medicinal plants by 76.06%, skills in planting and processing by 76.24%, and knowledge of marketing methods by 78.86%. After the program, participants demonstrated initiative in using herbal medicine to treat minor illnesses within their families and began utilizing home gardens to grow herbal plants. Furthermore, the village government plans to establish a business group for PKK mothers to strengthen the local economy. The follow-up of this activity is expected to involve collaboration between the village, health centers, and the community to enhance the sustainable use of herbal medicinal plants for health improvement.